Sosialisasi Pengembangan Keterampilan Partisipasi Sosial pada Pembelajaran Sejarah di SMA Negeri 3 Palu - Priyatna Prasetyawati; Zulaikhah Dwi Jayanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The problem of this community service is whether through this service, teachers and students can synergize by applying the strategy of developing social participation skills as one of the dimensions of skills that are highly recommended to achieve the objectives of history learning at SMA Negeri 3 Palu. The objectives that can be achieved in this service are (1) teachers and students can apply the strategy of developing social participation skills in learning history at SMA Negeri 3 Palu. (2) by developing social participation skills, it is hoped that the history learning process will no longer be boring or considered a soft subject. (3) by applying social participation skills, it is expected that history learning will be more challenging because history learning is not only memorized. The hope to be achieved through this community service is that teachers and students can synergistically process in learning history to improve competence not only knowledge, but attitudes and skills, especially in social participation skills must also be balanced so that students can participate in their environment to help solve societal problems and be skilled in the community environment, and can increase teacher competence in teaching creativity. Through socialization, mentoring and tracing in the form of observations, interviews and documents, it is hoped that teachers and students can be characterized as responsive and strong character.